Предмет: Математика,
автор: doenpink
Реши уравнение: 8⋅(9+x)−3x=6x−63. Ответ: x=
Ответы
Автор ответа:
0
8(9+x)-3=6x-63
64+8x-3x=6x-63
8x-3x-6x=-63-64
-1x= -127
x= -127:(-1)
x=127
Автор ответа:
1
Ответ:
8⋅(9+x)−3x=6x−63.
х=135
Пошаговое объяснение:
8⋅(9+x)−3x=6x−63.
72+8х-3х=6х-63
5х-6х=-63-72
-х=-135
х=135
Похожие вопросы
Предмет: Английский язык,
автор: КристинаУспасская
Предмет: Другие предметы,
автор: Vikyss08
Предмет: Русский язык,
автор: viktoriiazasor
Предмет: Математика,
автор: rtzg
Предмет: Математика,
автор: Veronika53535